Pengaruh Lingkungan Kerja Fisik, Motivasi Kerja dan Kerjasama Tim Terhadap Kinerja Karyawan Pada PT Adira Dinamika Multi Finance Tbk - Fitria, Nessa Rahma; Hidayati, Nur; Zamzam, Nurali Agus Najibul (FEB Universitas Maritim Semarang, 2025)
This study aims to analyze the effect of physical work environment, work motivation, and teamwork on employee performance at PT Adira Dinamika Multi Finance Tbk. The research employed a quantitative approach with a survey method involving all 51 employees as the total sample using a saturated sampling technique. Data were collected using a five-point Likert scale questionnaire developed from the theories of Herzberg, Luthans, and Tuckman. Validity and reliability tests were conducted to ensure instrument quality, while data were analyzed using multiple linear regression with SPSS version 26. Classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation, were performed to verify the model’s adequacy. The results indicate that the physical work environment, work motivation, and teamwork have positive and significant effects on employee performance, both partially and simultaneously. Among these variables, work motivation exerts the strongest influence on performance improvement. Overall, the three independent variables explain 84.2% of the variation in employee performance, while the remaining 15.8% is explained by other factors not included in the model. These findings highlight the importance of strengthening employee motivation, improving workplace conditions, and fostering a collaborative work culture to enhance human resource management effectiveness in the financial service industry.